Enhancement of in vitro transcellular absorption and in vivo oral bioavailability of apigenin by self-nanoemulsifying drug delivery systems - Vilasinee Hirunpanich Sato; Hitoshi Sato; Manaw Sangfuang; Jannarin Nontakham; Varaporn Buraphacheep Junyaprasert; Veerawat Teeranachaideekul; Boontida Morakul (Scientific Reports)
Abstract This study aims to develop a self-nanoemulsifying drug delivery system (SNEDDS) to solve the limited oral bioavailability problem of apigenin, a bioactive flavonoid. Apigenin-loaded SNEDDS consisting of Gelucire 44/14, Tween 80, and PEG 400 in the mass ratios of 25:37.5:37.5 and 30:35:35 were prepared, and designated as GTP2575 and GTP3070, respectively. The physicochemical stability at 30 and 40 ºC for 6 months was evaluated and a good stability was found. The in vitro transport of apigenin across Caco-2 monolayers from the SNEDDS and the in vivo pharmacokinetics in rats were investigated and compared with apigenin intact form. The in vitro permeation results demonstrated an increased transcellular permeability compared to the apigenin coarse powder (p < 0.05), while there was comparable permeation of apigenin in GTP2575 and GTP3070 formulations, with the permeability constants (Papp) being 2.97 × 10-5 and 3.13 × 10-5, respectively (p > 0.05). The pharmacokinetic analysis in rats revealed that the pharmacokinetic parameters, such as Cmax, AUC0-24, and AUC0−∞, were significantly higher with apigenin-loaded SNEDDS than with apigenin coarse powder (p < 0.05). Apigenin’s oral relative bioavailability increased by 3.8 and 3.3 times for GTP2575 and GTP3070, respectively, due to SNEDDS’s effect on solubilization and transcellular permeability. The in vivo acute oral toxicity according to OECD 425 was evaluated and revealed low toxicity with an LD50 exceeding 2,000 mg/kg in all apigenin’s formulations. These findings suggest that apigenin-loaded SNEDDS may represent a promising strategy for improving the oral delivery of apigenin.